Psychological factors associated with quarantine in times of contagion: A systematic review (European Journal of Health Research, 2020)
Current spread of a pandemic by the novel coronavirus (COVID-19) is a worldwide milestone. It has led to quarantine as a healthcare measure in the territories most affected. However, people with more negative emotional styles may run a higher risk of contagion by the disease, as both their physical and mental health are affected. The objective of this study was to identify in a systematic review, psychological factors associated with health during quarantine. For this purpose, a search was made of scientific articles in databases, such as Scopus, Web of Science, PsycINFO and CINAHL, where 62 documents were found, of which, after applying inclusion criteria, seven studies remained for their review. The results showed, first, that people in quarantine because of a pandemic had higher stress, anxiety, depression and distress. Second, that a positive emotional style was related to less risk of contagion of diseases. These results have implications for the practice, and especially for healthcare professionals who are indispensable in coping with disease in a pandemic. It would therefore be necessary to protect their health so that they, in turn, can offer quality care to patients in crises and emergencies.